Quality of Restructured Buffalo Meat Fillets extended with Hydrated Barley - Ahmad, S.R.; Sharma, B.D.; Irshad , A. (Journal of Meat Science, 2014)
The study was aimed at optimizing level of hydrated barley flour in restructured buffalo meat fillets. The hydrated barley flour at three levels viz. 8, 10, and 12 percent was used as extender replacing lean meat in the formulation of control restructured buffalo meat fillets. The extended fillets were evaluated for various physico-chemical and sensory properties and compared with the control. The cooking yield increased with barley flour extension and at 12 percent level, it was significantly higher (P<0.05) than control. Moisture percent was significantly higher (P<0.05) and fat percent significantly lower (P<0.05) at 10 and 12 percent levels when compared with control. Overall acceptability scores for all the treatment products were comparable to control. Various physico-chemical parameters including cooking yield as well as sensory scores indicated that restructured buffalo meat fillets containing hydrated barley flour up to 12 percent level were highly acceptable. The production cost of restructured buffalo meat fillets was reduced by 10.31 percent with barley flour extension. Thus, 12% level of extension of hydrated barley flour in the formulation of restructured buffalo meat fillets was selected to economize the processing technology for the production of restructured buffalo meat fillets.